Graphene Oxide-Based Nanocarriers for Cancer Imaging and Drug Delivery - You, Peihong; Yang, Yang; Wang, Mingwei; Huang, Xiaoyu; Huang, Xiao (Current Pharmaceutical Design, 2015)
Nano graphene oxide (nGO) is a member of graphene family, which is a novel, one-atom-thickness, two-dimensional carbon nanomaterial. In comparison with graphene, nGO contains much higher extent of reactive chemical functionalities such as hydroxyl, carbonyl, carboxyl, and epoxy group, so as to enable its easier biochemo-functionalization, higher biocompatibility, and greater potentials of applications in biomedicine fields. Up to now, nGO has attracted extensive research interests in nanomedicine and drug delivery systems for cancer imaging and therapy due to its unique biochemical and in vivo properties. This review generally describes the preparation, functionalization, and toxicity of nGO firstly, and then focuses on the studies of biomedical applications for cancer imaging and drug delivery.
Keywords: Cancer imaging